Implementasi Metode Pembelajaran Jelajah Alam Sekitas (JAS) untuk Meningkatkan Motivasi dan Keterampilan Proses Sains Mahasiswa pada Matakuliah Morfologi Tumbuhan - Royani, Ida; Imran, Ali; Dharmawibawa, Iwan Doddy (Bioscientist : Jurnal Ilmiah Biologi, 2024)
The aim of the research is to increase the motivation and science process skills of second semester biology students in the Plant Morphology course using the Environmental Exploration (JAS) method. The background to this research is the lack of direct use of learning resources from nature by students, learning resources usually come from books, direct materials and learning media provided by course lecturers. The subjects in this research were biology students at the Mandalika Education University (UNDIKMA) second semester of the 2023/2024 academic year. The type of research used is PTK using questionnaire instruments and observation sheets. The results of research on the implementation of the use of environmental exploration methods can increase students’ learning motivation in cycle II, showing the highest score, namely 168 and the lowest score, namely 129, with an average score of 148.34 from a total sample of 25 students. This indicates an increase in students’ learning motivation and can improve students’ science process skills in plant morphology courses in the 2023/2024 academic year.